Patterns of Care in Maintenance Therapy in US Patients Undergoing Definitive Chemoradiation for Stage 3 Non–Small Cell Lung Cancer (NSCLC). (February 2022) - Liu, Jason; Bratton, Emily; Yu, Xinyan; Ladbury, Colton; Wagner, Joseph; West, Howard; Massarelli, Erminia; Salgia, Ravi; Pathak, Ranjan; Villaflor, Victoria; Villalona-Calero, Miguel; Amini, Arya
Abstract : Objective: The recommended treatment for patients with unresectable stage 3 non–small cell lung cancer (NSCLC) is definitive chemoradiation followed by 1 year of maintenance durvalumab. Our objective was to assess the rate of maintenance durvalumab use after chemoradiation. Methods: Analyses were conducted in both open claims (IQVIA pharmacy and medical claims data) and adjudicated closed claims (IQVIA PharMetrics Plus Health Plan Claims Database). Patients with a lung cancer diagnosis between November 2017 and November 2020 who received definitive chemoradiation were included. Results: Of the 5802 NSCLC patients included in the open claims source, 1794 (31%) received durvalumab, 1403 (24%) received maintenance chemotherapy, and 2605 (45%) did not receive any maintenance therapy. Of the 239 NSCLC patients included in the closed claims source, 127 (53%) received durvalumab, 40 (17%) received maintenance chemotherapy, and 72 (30%) did not receive any maintenance therapy. The most common maintenance chemotherapy agents patients received were carboplatin, pemetrexed, and paclitaxel. Conclusions: The rate of durvalumab utilization was overall low in both the open and closed claims data sources (31% and 53%, respectively). It remains unknown what percent of eligible patients end up receiving durvalumab, as our analysis was unable to filter out patients who were unfit for durvalumab or if they had progression after chemoradiation. Future efforts are needed to increase maintenance durvalumab utilization and to determine how best to manage patients who are unfit for durvalumab.